SOD Derived from Bacillus amyloliquefaciens GF423 Has Protection Against Exercise-Induced Oxidative Stress in Healthy Subjects. (29th May 2020) - Nam, Yea-eun; Kim, Yunsoo; Lim, Yeni; Kim, Hye Jin; Kwon, Oran
Abstract: Objectives: Excessive reactive oxygen species (ROS) can cause cellular damage, causing a variety of degenerative diseases such as atherosclerosis, ischemic heart disease, and cancer. SOD is thought to play a central role in scavenging ROS generated in cells by enhancing the antioxidant defense system, including catalase and glutathione peroxidase. This study aims to test the hypothesis that exogenous SOD administration can help to protect against oxidative stress encountered at very early stages in the daily life of healthy subjects. Methods: A total of 80 healthy adults were assigned to either an intervention group consuming B. amyloliquefaciens GF423 SOD (250 IU/capsule) daily for 8 weeks or a placebo in a randomized, double-blind and parallel design. Aerobic exercise by a treadmill for 30 minutes at an intensity of 60% of the maximal oxygen consumption (VO2max ) of each subject was used to induce oxidative stress at the beginning and end of the experimental period. Blood and urine samples were collected immediately after and 30 min after the exercise challenge to measure biochemical markers related to oxidative stress and inflammation. Results: A single administration of exogenous SOD induced a marked decrease in urinary lipid peroxides and plasma pro-inflammatory cytokines as compared to placebo administration. Furthermore, repeated administration of exogenous SOD for eight weeks resulted in a significant improvement of erythrocyte redox balance. Conclusions: These findings suggest that the supply of exogenous SOD may be useful to enhance the antioxidant defense capacity and anti-inflammatory response in response to exercise-induced oxidative stress. Funding Sources: This work was supported by the Bio-Synergy Research Project (NRF-2012M3A9C4048761) from the Ministry of Science, ICT, and Future Planning, and the BK21PLUS (Brain Korea 21 plus) program (22a20130012143) from the Ministry of Education and the GenoFocus Inc, Republic of Korea.